2004
DOI: 10.1128/jvi.78.13.7186-7198.2004
|View full text |Cite
|
Sign up to set email alerts
|

Receptor (CD155)-Dependent Endocytosis of Poliovirus and Retrograde Axonal Transport of the Endosome

Abstract: Poliovirus (PV), when injected intramuscularly into the calf, is incorporated into the sciatic nerve and causes an initial paralysis of the inoculated limb in transgenic mice carrying the human PV receptor (hPVR/CD155) gene. Here, we demonstrated by using an immunoelectron microscope that PV particles exist on vesicle structures in nerve terminals of neuromuscular junctions. We also demonstrated in glutathione S-transferase pulldown experiments that the dynein light chain, Tctex-1, interacts directly with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 43 publications
5
91
0
1
Order By: Relevance
“…In HeLa cells, virus particles have been visualized inside endosome-like structures at early times postinfection, suggesting that poliovirus infection requires virus uptake into endosomes (49,82). This route of infection has also been reported for Hep-2 cells (84) and neural cells (59). However, other studies have concluded that poliovirus infection may not involve virus uptake via clathrindependent endocytosis (13,20,41,76), as infection has been reported not to be dependent on the low pH within endosomes (63) or on dynamin, a protein required for the formation of clathrin-coated pits (24).…”
mentioning
confidence: 71%
“…In HeLa cells, virus particles have been visualized inside endosome-like structures at early times postinfection, suggesting that poliovirus infection requires virus uptake into endosomes (49,82). This route of infection has also been reported for Hep-2 cells (84) and neural cells (59). However, other studies have concluded that poliovirus infection may not involve virus uptake via clathrindependent endocytosis (13,20,41,76), as infection has been reported not to be dependent on the low pH within endosomes (63) or on dynamin, a protein required for the formation of clathrin-coated pits (24).…”
mentioning
confidence: 71%
“…Furthermore, PV dissemination via the neural pathway has been found to rely on a fast retrograde axonal transport system and was inhibited by MAb p286 (34). Moreover, the efficient direct interaction of the hPVR cytoplasmic domain with Tctex-1, a light chain of cytoplasmic dynein (21), has been suggested to play an important role in retrograde transport, together with microtubule integrity (33). Cytoplasmic dynein, a minus-end-directed microtubule-based motor complex (13,14,17,43), is implicated in the transport of early and late endosomes, lysosomes, synaptic vesicles, and endoplasmic reticulum along microtubules (1,8,13,14,17,43).…”
mentioning
confidence: 99%
“…The brain stem is most likely the major target of EV71 infection (2, 8). However, neither the host cell receptor nor the neurotransmission route of EV71 is fully defined.As for poliovirus (PV), two possible routes by which the virus reaches the central nervous system (CNS) have been suggested: the virus either enters the CNS from the blood across the blood-brain barrier (BBB) or is transmitted to the CNS through peripheral nerves via retrograde axonal transport (1,3,14,23). Expression of certain gene segments would be responsible for determining the capacity of PV to spread to the CNS through bloodstream or neuronal pathways (18).…”
mentioning
confidence: 99%